Impact of Air Pollution on the Health of the Population in Parts of the Czech Republic - Sram, Radim J (International journal of environmental research and public health, 2020)
Thirty years ago, Northern Bohemia in the Czech Republic was one of the most air polluted areas in Europe. After political changes, the Czech government put forward a research program to determine if air pollution is really affecting human health. This program, later called the "Teplice Program", was initiated in collaboration with scientists from the United States Environmental Protection Agency (US EPA). This cooperation made possible the use of methods on the contemporary level. The very high concentrations of sulphur dioxide (SO2), particulate matter of 10 micrometers or less (PM10), and polycyclic aromatic hydrocarbons (PAHs) present in the air showed, for the first time, the impact of air pollutants on the health of the population in mining districts: adverse pregnancy outcomes, the impact of air pollution on sperm morphology, learning disabilities in children, and respiratory morbidity in preschool children. A surprising result came from the distribution of the sources of pollution: 70% of PM10 pollution came from local heating and not from power plants as expected. Thanks to this result, the Czech government supported changes in local heating from brown coal to natural gas. This change substantially decreased SO2 and PM10 pollution and affected mortality, especially cardiovascular mortality.
Keywords: pevné částice; Female; Europe; předškolní dítě; ženské pohlaví; Health; znečištění ovzduší; lidé; Air Pollution; Evropa; zdraví; těhotenství; Particulate Matter; Air Pollutants; Czech Republic; Child, Preschool; Česká republika; Pregnancy; látky znečišťující vzduch; Humans